DIGITALISASI PENDIDIKAN DAN DAMPAKNYA TERHADAP PEMBELAJARAN DI ERA SOCIETY 5.0 - Syarifuddin La Tiga; Suci Indasari; Siti Arfah; Saifudin Saifudin; Nilawati Tadjuddin (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
Educational digitalization is one of the main strategies for addressing learning challenges in the Society 5.0 era, which emphasizes the integration of technology and a human-centered approach. This study aims to analyze the effect of educational digitalization on learning motivation and learning outcomes, as well as the role of teachers’ digital competence in strengthening the effectiveness of digital learning. The research employed a quantitative approach with an explanatory research design, involving students and teachers at secondary education institutions that have implemented digital-based learning. Data were collected through Likert-scale questionnaires and documentation of learning outcomes, and were analyzed using multiple linear regression and moderation analysis. The results indicate that students’ digital literacy has a positive and significant effect on learning motivation (β = 0.42; p < 0.001) and learning outcomes (β = 0.36; p < 0.001). Teachers’ digital competence also has a significant effect on students’ learning outcomes (β = 0.29; p = 0.001) and strengthens the relationship between students’ digital literacy and learning outcomes (β = 0.29; p = 0.004), with a coefficient of determination (R²) of 0.53. In conclusion, educational digitalization is proven to enhance the quality of learning in the Society 5.0 era when supported by adequate student digital literacy and teachers’ digital competence.